Uji Aktivitas Antidiabetes In Vitro Ekstrak Etanol 96% Daun Karamunting (Melastoma malabathricum L.) dengan Metode Maserasi - Muthia, Rahmi; Afra, Fairuz Yaumil; Nurmansyah, Dian; Fauzana, Erwin; Istiqamah, Qanita (Journal of Pharmaceutical and Sciences, 2025)
Background: Diabetes mellitus remains a major global health issue, with rising prevalence due to population growth, aging, and lifestyle factors. Melastoma malabthricum L. has potential as an antidiabetic agent based on empirical data and in vivo study. Objective: To determine the content of secondary metabolite compounds contained in the extract of Karamunting leaves and to determine the activity and EC50 value of the extract for antidiabetes was evaluated using the Nelson-Somogyi method. Methods: This study used the phytochemical screening approach to identify the active chemicals. 96% ethanol was the solvent used in the maceration process to extract the leaves of M. malabathricum. The Nelson-Somogyi method was used to test the antidiabetic activity by calculated the sample's EC50 value on decreased glucose levels. The Nelson Somogyi method's antidiabetic activity was tested with a UV-Vis Spectrophotometer. It operated for 25 minutes at a wavelength of 740 nm. Results: Phenolic chemicals, flavonoids, saponins, steroids, and tannins all exhibited positive results from the phytochemical screening. After the addition of 96% ethanol extract of M. malabathricum leaves at gradually higher concentrations, the percentage decrease in glucose levels was 25.32%, 36.90%, 51.39%, 70.87, and 82.83% at concentrations of 1, 2, 3, 4, and 5 ppm. R2 = 0.9927 with y = 14.898x + 8.7747. Conclusion: 96% ethanol extract of M.malabathricum leaves contains several active substances, can reduce blood glucose levels and has an EC50 value of 2.76 ppm. Clinically, this implies a promising therapeutic potential with lower required dosages.